2006
DOI: 10.1111/j.1532-950x.2006.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Colonic Luminal Pressure to Predict Outcome After Surgical Treatment of Strangulating Large Colon Volvulus in Horses

Abstract: CLP measurements based on a single hospital population of horses with LCV should be used with caution for other hospital populations of LCV. CLP may be only one of many variables needed for predicting outcome of horses with strangulating LCV, especially after LCRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 5 publications
7
44
1
1
Order By: Relevance
“…Broodmares are more likely to develop large colon volvulus than mares that have never foaled and males . Predominance of spring and summer occurrence, observed severe pain, anticlockwise/dorsomedial direction, 360° of rotation and location adjacent to the caecal base of colonic volvulus, palpation of gas distended large colon via rectal examination, close proximity to foaling date and manual anatomic correction as the primary surgical treatment were also similar between the current study and that observed in other reports . The recurrence prevalence in the current study of approximately 15% was higher than those previously reported of 5% and 8% .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Broodmares are more likely to develop large colon volvulus than mares that have never foaled and males . Predominance of spring and summer occurrence, observed severe pain, anticlockwise/dorsomedial direction, 360° of rotation and location adjacent to the caecal base of colonic volvulus, palpation of gas distended large colon via rectal examination, close proximity to foaling date and manual anatomic correction as the primary surgical treatment were also similar between the current study and that observed in other reports . The recurrence prevalence in the current study of approximately 15% was higher than those previously reported of 5% and 8% .…”
Section: Discussionsupporting
confidence: 87%
“…Documentation of this association reinforces the importance of reduced presurgical treatment colic duration as it affects survival in horses with large colon volvulus, and focuses future education on timely referral and its positive impact on colic treatment outcomes . Other identified factors associated with survival rate in the present study, including PCV at admission , surgical duration , operative hypotension , and post operative heart rate and manure consistency , have been similarly observed in other reports.…”
Section: Discussionsupporting
confidence: 86%
“…Large colon‐related diseases are commonly associated with colic in horses and account for more than one‐third of horses undergoing exploratory celiotomy for gastrointestinal pain . Colectomy is performed for salvage in cases with severe disease and intestinal necrosis, such as in horses with strangulating large colon volvulus . Colectomy is also performed in some cases to prevent colic recurrence following repeated colonic disease, such as large colon displacement .…”
Section: Introductionmentioning
confidence: 99%
“…However, specific anastomosis techniques have not been evaluated or compared with respect to patient outcomes. The reported percentage of horses that survive to hospital discharge following colectomy is between 60% and 80% . While on the whole these percentages are comparable between techniques, comparison of selected reports might suggest better outcomes with end‐to‐end anastomoses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation